Asus / Nabila Rashid - Rashid, Nabila (2022)
As a student in UiTM Arau, every student needs to undergo a case study project since it is a part of the study. So, for this purpose, we got the opportunity to research a company which manufactured the technology product, which is Asus Technologies, multinational computer and phone hardware and electronics company, currently headquartered in Beitou District, Taipei, Taiwan. In the first part of the project report, we have collected the general information of the company. Primary sources are used to gather all the information and not forget to mention some of them come from the secondary source as well. Specialized subject study is contained in the second part of the report. Objective of the project is to work on the background, organizational structure, products and services that Asus Technologies provides. Next, we study the technology of Asus Technologies electronic components, as well as business, we find that the marketing and its operational strategy that are used by this company to promote their products are very quite interesting. What goals means for a business is what a business unit wants to achieve. But an action plan for getting the goals is called strategy. To achieve goals, every business must design their strategy, consisting of a marketing strategy, and effective management. In this case study, we analysed the strengths, weaknesses, opportunities and threats of this company in the real business world by using SWOT analysis. Thus, from the needs and demands from the existing consumers of this company, we analysed and found a solution to overcome and to fulfil their needs in Consumer Trend Canvas (CTC) analysis, which makes it our innovation to become a continuation inside the new Product Development task.